2011
DOI: 10.1007/s13181-011-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Relay Pentobarbital Toxicosis in a Dog

Abstract: Sodium pentobarbital and phenytoin are common constituents of veterinary euthanasia solutions in the United States. Relay, or secondary, barbiturate toxicosis has been reported in carnivorous animals that have fed from the carcasses of euthanized livestock. This case report presents barbiturate toxicosis in a dog. A 2-year-old female spayed Australian shepherd presented comatose 2 h after ingesting an unknown substance on the beach. The material was retrieved from the stomach by gastric lavage and visually ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Prolonged (36 hr) sedation occurred in a dog that consumed tissue possibly from a humpback whale euthanized with pentobarbital (and other drugs) 23 days previously in the same vicinity (Bischoff et al 2011). Even when deep burial of euthanized animals is possible, detection of pentobarbital in surface waters and decades-long persistence in ground waters is a potential concern (Eckel et al 1993;Peschka et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged (36 hr) sedation occurred in a dog that consumed tissue possibly from a humpback whale euthanized with pentobarbital (and other drugs) 23 days previously in the same vicinity (Bischoff et al 2011). Even when deep burial of euthanized animals is possible, detection of pentobarbital in surface waters and decades-long persistence in ground waters is a potential concern (Eckel et al 1993;Peschka et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the longer TTD during chemical euthanasia, in some cases it will cause less suffering than if inappropriate physical methods are applied or are applied incorrectly. Finally, possible eco-toxicological hazards may occur due to residues bioaccumulating in the environment and there is the possibility of secondary toxicosis [16,[47][48][49]-this is one of the primary reasons that such chemical methods are not employed in NZ stranding events (L. Boren DOC, pers. comm.).…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Notwithstanding that to date only a single case has been uncovered, this discovery should be sufficiently compelling to instigate routine monitoring, notably where deliberate poisoning of animals is a known practice, as in many parts of Europe (Guitart et al 2010). Bischoff et al (2011) reported on a dog that evidently fed on tainted whale blubber encountered on a beach where, three weeks prior, a stranded juvenile humpback whale was euthanized and necropsied. Complete removal of the whale carcass was attempted but proved challenging.…”
Section: Emerging Areas Of Potential Exposure or Exposure Prevention That Require Follow-upmentioning
confidence: 99%
“…Samples of the dog's urine and from tissue recovered at the beach both tested positive for pentobarbital and the anticonvulsant phenytoin. The authors noted that while the dog was not determined with certainty to have ingested the pentobarbital-tainted blubber, it appeared to have been the likeliest source of exposure (Bischoff et al 2011). A workshop summary report on humane euthanasia protocols for stranded cetaceans highlight that "when considering chemical euthanasia, it must be remembered that the size of the animal also necessitates large quantities of euthanasia agents" (IWC 2015).…”
Section: Emerging Areas Of Potential Exposure or Exposure Prevention That Require Follow-upmentioning
confidence: 99%